Influence of phospholipids on the crystallization of waxes in sunflowerseed oil - Rivarola, Gustavo José (1988)
The effect of lecithins on wax crystallization in sunflowerseed oil was studied. The results showed that the presence of lecithins does not modify the nucleation stage, but decreases the crystalline size. Lecithin has a minimal effect on viscosity and does not change the wax/oil equilibrium ratio. It is proposed that the main mechanism of action of lecithin involves the partial adsorption on the surface of the wax crystals interfering with their growth.